Evaluation of the mutant selection window of danofloxacin against Actinobacillus pleuropneumoniae in an in vitro dynamic model - Zhang, Longfei; Wang, Hongjuan; Bai, Yilin; Wang, Lei; Bai, Yueyu; Hu, Jianhe (Frontiers in Veterinary Science, 2023)
The rapid emergence and widespread spread of multidrug-resistant (MDR) bacteria is a serious threat to human and animal health. Especially the Gram-negative (G-) bacteria containing MCR gene have developed resistance to colistin, which may result there were no antibiotics available for MDR infections treatment. The pharmacokinetic/pharmacodynamic (PK/PD) integration model based on mutant selection window (MSW) theory is an important guiding method to optimize the dosage regimen to prevent the emergence and spread of drug-resistant bacteria. Actinobacillus pleuropneumoniae is a serious pathogen of porcine pleuropneumonia. In this study, we intend to use in vitro dynamic infection model to study the prevention of drug-resistant mutations of danofloxacin against A. pleuropneumoniae. A peristaltic pump was applied to establish an in vitro dynamic infection model to simulate the pharmacokinetics of danofloxacin in plasma, and to study the MSW of danofloxacin against A. pleuropneumoniae. The results showed that the peristaltic pump in vitro infection model was successfully established to simulate the dynamic changes of danofloxacin in the plasma of pigs, and the pharmacokinetic and pharmacodynamic data were obtained. Then the relationship between PK/PD parameters and antibacterial activity was analyzed by the Sigmoid Emax model. The results showed that AUC24h/MIC99 had the fittest relationship with antibacterial activity. The AUC24h/MIC99 values for antibacterial effect, bactericidal effect and eradication effect were 2.68 h, 33.67 h, and 71.58 h, respectively. We hope these results can provide valuable guidance when using danofloxacin to treat A. pleuropneumoniae infections in clinic.